2022
DOI: 10.1002/smr.2455
|View full text |Cite
|
Sign up to set email alerts
|

Scaled agile framework. Dealing with software process‐related challenges of a financial group with the action research approach

Abstract: This article reports on a domain-specific software development venture at Nordea. We explore organizational constraints, challenges, and corrective actions undertaken when scaling the agile development approach of their Core Banking Platform program. The fit and required customizations of the rather complex and rigid SAFe framework in a policy-heavy financial institution are audited against the organic growth of the program. In a qualitative study with three cycles using the Action Research method, both organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 85 publications
1
8
0
1
Order By: Relevance
“…Kerangka kerja memberikan langkahlangkah dan metode dalam melakukan penelitian [24]. Sistematis kerangka penelitian yang jelas akan memberikan kemudahan dalam memecahkan masalah dan mempermudah deteksi jika terdapat kekurangan dan kesalahan dalam penelitian [25]. Tahapan penelitian ini disajikan pada Gambar 1.…”
Section: Metodologi Penelitianunclassified
“…Kerangka kerja memberikan langkahlangkah dan metode dalam melakukan penelitian [24]. Sistematis kerangka penelitian yang jelas akan memberikan kemudahan dalam memecahkan masalah dan mempermudah deteksi jika terdapat kekurangan dan kesalahan dalam penelitian [25]. Tahapan penelitian ini disajikan pada Gambar 1.…”
Section: Metodologi Penelitianunclassified
“…Departmental borders and, more generally, organizational silos [2] in classical hierarchical corporate organizations lead to the fact that agile transformation efforts frequently fail reaching the critical mass of entities required to make the change happen on a large scale. Overcoming these boundaries requires specific strategies that typically rely on the presence and active involvement of agile trainers and coaches in a huge number of departments [3]. These coaches have the mission to introduce agile mindsets and practices in a way that is most appropriate to the current organizational culture and practices of that very unit.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nonetheless, as the vast majority of software development projects are unique, they cannot be properly supported by any off-the-shelf framework implemented in its original, textbook format. [4][5][6][7][8][9][10][11][12][13] Besides, not all organizations are ready to fully implement any framework in a one-time shift regarding organizational, cultural, and technical aspects, 13,14 whereas there are no gradual approaches or guidelines for large-scale agile transformation. 15,16 Indeed, previous studies have reported numerous challenges while adopting such frameworks, 4,6,17 including a mismatch between framework and organization, 6,7,13 controversies within the framework, [18][19][20] complex organization setup, 15,20 changes in management structure, 6,15,19,21,22 fluctuating company's policies, 15,19,21 and change resistance.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Besides, not all organizations are ready to fully implement any framework in a one-time shift regarding organizational, cultural, and technical aspects, 13,14 whereas there are no gradual approaches or guidelines for large-scale agile transformation. 15,16 Indeed, previous studies have reported numerous challenges while adopting such frameworks, 4,6,17 including a mismatch between framework and organization, 6,7,13 controversies within the framework, [18][19][20] complex organization setup, 15,20 changes in management structure, 6,15,19,21,22 fluctuating company's policies, 15,19,21 and change resistance. 15,19,20 Not surprisingly, it has been acknowledged that agile methods often need to be tailored to accommodate specific situations [6][7][8]12,14,[23][24][25] or issues (e.g., risk management).…”
mentioning
confidence: 99%
See 1 more Smart Citation